Sex‐related and non‐sex‐related comorbidity subtypes of tic disorders: a latent class approach. (7th October 2013) - Rodgers, S.; Müller, M.; Kawohl, W.; Knöpfli, D.; Rössler, W.; Castelao, E.; Preisig, M.; Ajdacic‐Gross, V.
<x xml:space="preserve">Abstract</x> Background and purpose Recent evidence suggests that there may be more than one Gilles de la Tourette syndrome (GTS)/tic disorder phenotype. However, little is known about the common patterns of these GTS/tic disorder‐related comorbidities. In addition, sex‐specific phenomenological data of GTS/tic disorder‐affected adults are rare. Therefore, this community‐based study used latent class analyses (LCA) to investigate sex‐related and non‐sex‐related subtypes of GTS/tic disorders and their most common comorbidities. Methods The data were drawn from the PsyCoLaus study (n = 3691), a population‐based survey conducted in Lausanne, Switzerland. LCA were performed on the data of 80 subjects manifesting motor/vocal tics during their childhood/adolescence. Comorbid attention‐deficit hyperactivity disorder (ADHD), obsessive‐compulsive disorder, depressive, phobia and panic symptoms/syndromes comprised the selected indicators. The resultant classes were characterized by psychosocial correlates. Results In LCA, four latent classes provided the best fit to the data. We identified two male‐related classes. The first class exhibited both ADHD and depression. The second class comprised males with only depression. Class three was a female‐related class depicting obsessive thoughts/compulsive acts, phobias and panic attacks. This class manifested high psychosocial impairment. Class four had a balanced sex proportion and comorbid symptoms/syndromes such as phobias and panic attacks. The complementary occurrence of comorbid obsessive thoughts/compulsive acts and ADHD impulsivity was remarkable. Conclusions To the best of our knowledge, this is the first study applying LCA to community data of GTS symptoms/tic disorder‐affected persons. Our findings support the utility of differentiating GTS/tic disorder subphenotypes on the basis of comorbid syndromes.